Solving MDPs with thresholded lexicographic ordering using reinforcement learning - Tercan, Alperen, author; Prabhu, Vinayak S., advisor; Anderson, Charles W., advisor; Chong, Edwin K. P., committee member (Colorado State University. Libraries, 2022)
Multiobjective problems with a strict importance order over the objectives occur in many real-life scenarios. While Reinforcement Learning (RL) is a promising approach with a great potential to solve many real-life problems, the RL literature focuses primarily on single-objective tasks, and approaches that can directly address multiobjective with importance order have been scarce. The few proposed approach were noted to be heuristics without theoretical guarantees. However, we found that their practical applicability is very limited as they fail to find a good solution even in very common scenarios. In this work, we first investigate these shortcomings of the existing approaches and propose some solutions that could improve their practical performance. Finally, we propose a completely different approach based on policy optimization using our Lexicographic Projection Optimization (LPO) algorithm and show its performance on some benchmark problems.